APLIKASI SPASIAL SEBARAN SARANG NYAMUK UPAYA 3M DAN ANGKA BEBAS JENTIK - Darwel Darwel; Vivin Sri Wahyuningsih (Jurnal Kesehatan Lingkungan, 2018)
Eradication of Mosquito Nest and 3M Efforts is a way to prevent Dengue Fever. The success of PSN activities through 3M Plus can be measured by the larvae free rate (ABJ). ABJ in the working area of ​​Lubuk Sikaping Health Center is 79.3% which is still below the National target of yaitu 95%. The existence of dengue vector larvae is very dependent on the existence of mosquito breeding places Aedes aegypti and the behavior of the community in eradicating mosquito nests. The purpose of this study was to determine the spatial distribution of mosquito nests and 3M efforts towards ABJ in the working area of ​​Lubuk Sikaping Health Center in 2018. This type of research was observational with design cross sectional and used the GIS approach which was carried out in February - June. The research sample was 92 houses with The sampling technique in this study uses Purposive sampling. The data used are secondary data and data observation direct which are analyzed univariately and spatially. The results of study the spatial showed that the spatial distribution of ABJ in the study area did not meet the quality standards marked in red on the map. The most common type of containers found in Nagari Pauh, for the most common larvae found in Nagari Durian Tinggi. While 3M's efforts are most carried out in Nagari Pauh. The use of Geographic Information Systems can help in displaying a lot of information clearly, presenting information on the distribution of cases and risk factors for spreading DHF spatially through maps, as well as by spatial approach it can be known areas that are vulnerable to dengue disease